2018
DOI: 10.1088/1755-1315/157/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Shading effect on generative characters of upland red rice of Southeast Sulawesi, Indonesia

Abstract: Abstract. Upland red rice (Oryza sativa) contains anthocyanin, a phenolic compounds that can act as antioxidants and functional food for human dietary. The content of functional food on upland red rice is influenced by shading condition, but the production is also influenced by environmental condition, especially the availability of light. The study aims is to assess and analyze the effect of shade on the growth and production of upland red rice. The research was conducted using the quantitative method to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Moreover, shading stress decreased the dry matter accumulation of rice plants, as well as the grain weight. Plant productivity was found to be mainly controlled by the photosynthesis rate since reduced light intensity generally reduced the amount of source [11,25]. A previous study reported that shading stress reduces the supply of photosynthetic products, thereby remarkably decreasing starch biosynthesis in grains and postponing caryopsis development [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, shading stress decreased the dry matter accumulation of rice plants, as well as the grain weight. Plant productivity was found to be mainly controlled by the photosynthesis rate since reduced light intensity generally reduced the amount of source [11,25]. A previous study reported that shading stress reduces the supply of photosynthetic products, thereby remarkably decreasing starch biosynthesis in grains and postponing caryopsis development [26].…”
Section: Discussionmentioning
confidence: 99%
“…This factor causes plants to adapt to survive and increases photosynthesis sources, stimulating the production of more anthocyanin in plants compared to plants grown under normal light conditions. In addition, anthocyanin is degraded if the light intensity is coupled with too high a temperature [11]. A previous report showed that anthocyanins in shoot and rice grain are sensitive to low light intensity, which suggests that anthocyanins could serve as a target compound for investigating low-light stress conditions [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 90% of the national rice production is supplied from irrigated paddy fields which are partly conserved for various purposes outside agriculture. Several programs have been implemented to maintain rice sustainability [5] and to increase rice stock levels through increase production capacity [6][7][8][9], lowering level consumption, and consuming local food as sources of carbohydrate [4], as well as expanding planting areas. Although numerous attempts have boosted rice production [10,11] grain yields have remained stagnant [12].…”
Section: Introductionmentioning
confidence: 99%